The politics of evolution : morphology, medicine, and reform in radical London - Desmond, Adrian J., 1947- (Science and its conceptual foundations., 1989)
Looking for the first time at the cut-price anatomy schools rather than genteel Oxbridge, Desmond winkles out pre-Darwinian evolutionary ideas in reform-minded and politically charged early nineteenth-century London. In the process, he reveals the underside of London intellectual and social life in the generation before Darwin as it has never been seen before." The Politics of Evolution is intellectual dynamite, and certainly one of the most important books in the history of science published during the past decade."--Jim Secord, Times Literary Supplement. "One of those rare boo